THE STUDY OF THE IMAGERY OF IDIOMS WITH SOMATISMS IN THE CANADIAN VERSION OF THE FRENCH LANGUAGE, STANDARD FRENCH AND THE ENGLISH LANGUAGE - V.V. Teganyuk (Многоязычие в образовательном пространстве, 2023)
The article presents a comparative study of the imagery of the phraseological fund of the Canadian version of the French language, standard French and the English language. The purpose of the research is to describe the main ways of forming idioms with somatic components based on the material of the designated languages. The main objectives of the study are to identify specific, unique, as well as universal ways of reflecting the reality surrounding a person on the basis of figurative idioms with somatic components, to determine the main types of displacement and reconsideration of the meaning of a free combination of words that led to the creation of an idiom. The novelty of the work lies in the fact that for the first time it generalises the knowledge of somatisms’ imagery in the phraseological fund of the languages being compared. For correct understanding of idioms, it is necessary to trace the connection between the meaning of a free word combination and the way of its acquiring expressiveness, evaluative judgment through various means of creating an image. The anthropocentric nature of language as a whole suggests that a human being in general and parts of human body, in particular, are a measure and standard for describing and reflecting reality phenomena. The conclusion is made that somatisms in three languages under consideration are highly productive; most idioms resulted from metaphorical reconsideration, metaphorical transfer, or figurative comparison; idioms resulting from metaphorisation prevail in quantitative terms.